Prevalence and severity of anxiety, depression, and stress among optometry students in Nigeria: A cross-sectional study - Michael Agyemang Kwarteng; Osamudiamen McHillary Ogiemudia; Bernadine N. Ekpenyong; Okechi U. Amaechi; Grace Ogbonna; Edith I. Daniel-Nwosu; Ngozika Esther Ezinne; Oforbuike Onyebuchi Ike; Kelechi C. Ogbuechi; Uchechukwu Levi Osuagwu (PLoS ONE, 2026)
Purpose To assess the prevalence and severity of anxiety, depression, and stress among optometry students in Nigeria, and to identify demographic factors associated with mental distress. Methods A cross-sectional, web-based survey was administered to optometry students from 10 Nigerian universities between 16 April and 18 November 2024, with an estimated sample size of 427. Mental health status was evaluated using the Depression, Anxiety, and Stress Scale-21 items (DASS-21). Collected data included age, gender, year of study, marital status, and DASS-21 scores. Descriptive statistics summarized demographic characteristics and the prevalence of symptoms. Binary logistic regression was used to identify associations between demographic variables and mental health outcomes, with significance set at p < 0.05. Results A total of 474 students participated (mean age: 23 ± 3 years; 54.6% female; 94.1% unmarried). Overall, 51.1% experienced depressive symptoms, with 14.6% reporting severe or extremely severe symptoms. Severe anxiety was reported by 36.5%, and 25.1% experienced concurrent symptoms of anxiety, depression, and stress. Nearly half (49.2%) had at least two coexisting mental health conditions, indicating a significant emotional burden and potential impact on academic performance. Female students had significantly higher odds of experiencing depression (OR: 1.66; 95% CI:1.15–2.39) and overall mental distress (OR: 1.58; 95% CI: 1.03–2.43) compared to males. Conclusion This study revealed a high prevalence of mental health conditions among Nigerian optometry students, with one in four experiencing a comorbid of all three conditions. Female students were more likely to report adverse mental health outcomes. These findings underscore the urgent need for structured mental health support and preventive interventions within optometry training programs in Nigeria.